Sosialisasi K3 Dan 5R Pada Bengkel May Car Bodyworks - Gurning, Ridho Hans; Arohman, Abdul Wahid; Shalihah, Adinda Rahmah (Journal of Community Services in Sustainability, 2025)
Basically, every job will have its own safety hazard risk factors, especially the automotive industry. Automotive industry work practices have Occupational Safety and Health (K3) risks for all workers in the work environment. Potential hazards that will be faced include exposure to chemicals, infections, allergies, electricity and physical such as slipping, falling, being scratched, stabbed, and hit which depend on the type of activity carried out in the area. Seeing aspects of the physical work environment such as the layout of practice equipment, personal protective equipment, work clothes, cleanliness of the room, lighting, irrigation, air conditioning in the work space is very important in creating a safe environment free from the risk of accidents or occupational diseases. This is what drives the Abdimas team to encourage socialization and implementation of K3 and 5R at the May Car Bodyworks Workshop with the aim of increasing efficiency, productivity, and quality in work activities at the Workshop. This activity uses a descriptive qualitative method, where the technique of collecting data information is selected in a specific way, and uses observation methods with interviews and documentation and is analyzed in the application. The results obtained are in the form of a report on the implementation and application of the 5R program in the Workshop and can implement the 5R and K3 culture programs.